An evaluation of gonadotropin-releasing hormone analogue administered to gilts and sows on subsequent reproductive performance and piglet birth weight. Issue 1 (December 2016) - Vangroenweghe, Frédéric; Goossens, Lieve; Jourquin, Jan
Abstract Background The present study investigated the effect of peforelin (Maprelin®), a gonadotropin-releasing hormone (GnRH) analogue, administration in gilts, primiparous and pluriparous sows in a high productive farm on sow reproductive performance and piglet quality at birth. Methods In a 400 sow herd, gilts, primiparous and pluriparous sows were randomly allocated to 2 groups: peforelin treated (peforelin = P-group) or no treatment (control = C-group). Animals were injected 48 h after the last altrenogest treatment (gilts) or 24 h post weaning (sows). Weaning-to-estrus interval (WEI), estrus rate (ER), farrowing efficiency index (FEI), farrowing rate (FR), number of total (TBP), live (LBP) and stillborn piglets (SBP), mummies (MM) and live piglet index (LPI) were assessed and compared between treatment groups. To assess piglet quality at birth, 6033 piglets from 426 litters were weighed individually within 24 h after birth (BW; birth weight). Results No significant difference between treatment groups could be observed for WEI, TBP, LBP, SBP and MM. The ER was significantly (P = 0.0119) higher (93.2 %) in the P-group as compared to the C-group (87.2 %). Peforelin treatment did not affect farrowing rate. Both FEI and LPI were significantly (P = 0.0078) better in the P-group as compared to the C-group. Overall, no effect of peforelin treatment on piglet birth weight could be observed, although specific subcategories (1st parity and older (5+ parity) sows) did have a significant impact of treatment on birth weight. During late summer (August-September) all treated gilts and sows took advantage from peforelin treatment with a significant improvement of piglet birth weight. Conclusion Peforelin treatment had a significant impact on ER, FEI and LPI. Moreover, piglet birth weight improved for specific sow subcategories (1st parity and older sows) and for all gilts and sows during the late summer infertility period.